A Deeper Look into Type 1 Diabetes – Imaging Immune Responses during Onset of Disease - Christoffersson, Gustaf; von Herrath, Matthias G. (Frontiers in Immunology, 2016)
Cytotoxic T lymphocytes execute the killing of insulin-producing beta cells during onset of type 1 diabetes mellitus (T1D). The research community has come far in dissecting the major events in the development of this disease, but still the trigger and high-resolved information of the immunological events leading up to beta cell loss are missing. During the past decades, intravital imaging of immune responses has led to significant scientific breakthroughs in diverse models of disease, including T1D. Dynamic imaging of immune cells at the pancreatic islets during T1D onset has been made possible through the development of both advanced microscopes, and animal models that allow long-term immobilization of the pancreas. The use of these modalities has revealed a milling microenvironment at the pancreatic islets during disease onset with a plethora of active players. Clues to answering the remaining questions in this disease may lie in intravital imaging, including how key immune cells traffic to and from the pancreas, and how cells interact at this target tissue. This review highlights and discusses recent studies, models, and techniques focused to understand the immune responses during T1D onset through intravital imaging.